How Efficient are Islamic Banks in Indonesia, Saudi Arabia, and the United Kingdom? - Suhail Suhail; Mohamad Soleh Nurzaman (Faculty of Economic and Business, 2020)
This research aims to analyze the efficiency level of 13 Islamic Banks in Indonesia, Saudi Arabia, and the United Kingdom from 2015 to 2019. The calculation of the efficiency level in this study is relative, not absolute. This study uses the Data Envelopment Analysis (DEA) method and source data from Bankscope and Bank Focus. This research consists of 3 input variables that are Total of Assets (X1), Staff Expenses (X2) and Total Deposit (X3), and 2 Output that is Income (Y1) and Loan (Y2). This research finds that the overall efficiency level of 13 Islamic banks in Indonesia, Saudi Arabia, and the United Kingdom are fluctuating. According to the result, the Islamic banks in Saudi Arabia is more efficient than in Indonesia and the United Kingdom. There are some inefficient variables—the solution for this inefficiency problem achieve by employing managerial simulation generated by DEA. This study implies that Islamic banks should reduce wasteful variables and optimize the variables that improve the efficiency.JEL Classification: C1, F30, G20, G21How to Cite:Suhail., & Nurzaman, M. S. (2020). How Efficient are Islamic Banks in Indonesia, Saudi Arabia, and the United Kingdom?. Etikonomi: Jurnal Ekonomi, 19(2), 237-270. https://doi.org/10.15408/etk.v19i2.15862.